The dilemma faced by political office bearer-cum senior managerial employee in exercising their labour rights : a South African perspective - Mangena, Kgwara Calvin (My University, 2024)
This study analyses the precarious situation of between a ‘rock’ and a ‘hard place’ political office bearers-cum- senior managerial employees regularly find themselves in at the workplaces when exercising their labour rights. The study investigates the impact of the conflict of interest that manifests itself when these senior employees are expected to discharge their duties during an industrial action. Political office bearers-cum-senior managerial employees in this context refer to employees who also hold political offices. In terms of the Municipal Systems Amendment Act,1 a political office in relation to a political party or structure means: “the position of chairperson, deputy chairperson, secretary, deputy secretary, treasurer or an elected or appointed decision-making position of a political party nationally or in any province, region or area in which the party operates.” In the context of this study, employees who hold political office will refer to employees occupying positions of power in their employee organizations (and not political parties) such as those listed above by the Act and who also occupy senior and more influential positions such as senior managers or directors in an employment organogram. The dilemma arises out of a hard choice these managers have to embark on between collegiality and solidarity towards their fellow colleagues who may at times be their comrades and their trade union respectively on one hand and their common law duty of loyalty and trust towards their employers on the other hand. The study focuses on what role these highly ranked employees should play in the event of a labour dispute where the employer may sometimes respond to a strike action by enforcing a lockout or alternatively, in the event of a protest action where the employer may sometimes instruct the political office bearer-cum-senior employee to provide the employer with a documentary evidence in the form of a list of striking employees who have ‘downed tools’ and not report for duty for the purpose of the employer implementing the ‘no work, no pay’ rule2 given the fact that these senior employees are clothed first with the responsibility of being the employer’ representatives 1 Municipal Systems Amendment Act 3 of 2022, (Hereafter MSAA). 2 See Government Gazette No 21050 of 2000 titled ‘Regulations Regarding the Role of Managers Prior to Strike Action.’ and an integral part of management at the workplaces and therefore enforcing the employer’s instructions at the workplace and second to discharge discipline against their junior employees and colleagues who may sometimes be their comrades in their employee unions for work-related misconducts (School managers for an example have the responsibility to charge their fellow colleagues for acts regarded as misconduct). Strikes as used in the context of this study will in some instances also imply protests action especially when dealing with employers and employees in the public sector. The study also juxtaposes the seemingly compromised position of the political office bearer-cum- senior employee during a lockout or alternatively during a protest action. The study puts a spotlight on the dilemma these shop stewards-cum-managers face during the period of a lockout or in the event of a protest action. The preliminary findings of this study confirms that this conflict of interest highly compromises these senior employees and subsequently brings the employment relationship into disrepute.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2024
Keywords: Conflict of interest; Employer; Labour disputes; Lockout; Political office bearers; Protest action; Senior managerial employees; Shop stewards; Strikes; Labour disputes -- South Africa; Conflict of interests; Shop stewards; Employee rights